Comparing endovascular and open reconstruction for TASC-II D aortoiliac disease: a propensity score analysis - Basílio-Martins, Mariana; Pereira-Neves, António; Domingues-Monteiro, Diogo; Costa-Pereira, Tiago; Marques-Vieira, Mário; Vidoedo, José; Rocha-Neves, João (International Surgery Journal, 2023)
Background: Aortoiliac disease management remains a subject of ongoing debate, with a shift in focus toward endovascular techniques, even in complex cases. This study aimed to evaluate and compare the safety and results of open surgery with endovascular surgery for treating TASC-II D aortoiliac lesions. Methods: From January 2013 to February 2021, the clinical data of 89 patients revascularized with symptomatic TASC ΙΙ D AID were analyzed in a prospective cohort study. The patients were divided into two groups: open repair (61 patients) and endovascular treatment (28 patients). Baseline characteristics, preoperative and postoperative imaging, operation procedure reports and follow-up were reviewed and analyzed. Kaplan-Meier survival analysis, multivariate Cox regression, and a Propensity Score Matching (PSM) analysis were used to evaluate the relevance between risk factors and surgical technique. Results: Open repair had a higher technical success rate (100% vs. 73.7%, p=0.01). 30-day major adverse cardiovascular (MACE) and limb (MALE) events showed no differences between both groups (PSM: 1 (4.8%) vs. 0, p=0.462 and 1 (4.8%) vs. 2 (13.3), p=0.235, respectively). Cox multivariable regression proportional hazard ratio showed no significant differences in terms of MALE between open and endovascular revascularization at 36 months (hazard ratio, HR 1.31 95% CI 0.56-3.06, p=0.54), even after PSM (HR 1.63 95% CI 0.58-4.55, p=0.35). Moreover, MACE and all-cause mortality also didn´t show a statistically significant difference between groups (HR 0.77 95% CI 0.22-2.64, p=0.67 and HR 0.97 95% CI 0.27-3.46, p=0.96). Conclusions: Open and endovascular techniques are safe and effective treatments for complex AIOD. It is expected to have a higher technical success rate with open repair; however, there are no significant differences in MACE or MALE between these two approaches.